HUBUNGAN PENGETAHUAN, AKTIVITAS FISIK DAN STATUS GIZI DENGAN KEJADIAN HIPERURISEMIA DI WILAYAH KERJA PUSKESMAS TELAGA BIRU KOTA PONTIANAK - Atika Fitriyani; Shelly Festilia A (Pontianak Nutrition Journal (PNJ), 2018)
Increasing life expectancy in Indonesia affects the elderly population in Indonesia is getting higher. The elderly is a group have risk for hyperuricemia,Â  characterized by a buildup of uric acid that cause joint pain. Based on the data Riskesdas 2013, disease prevalence according to diagnose in Indonesia (24,7%) and in West Borneo (22,3%). It can be affected by physical activity, nutritional status and food selection behavior based on the level of knowledge. This research aimed to determine the correlation of knowledge, physical activity and nutritional status with the incidence of hyperuricemia of Telaga Biru Public Health Center, Pontianak 2016. This research was a cross sectional which sampling technique is accidental sampling with the number of sample 65 samples. The statistical test used is chi square test. The result of this research most of the knowledge level of respondents in less category (58,5%), physical activity in light category (73,8%) and obesity nutritional status (33,8%). The result of analysis with chi square test showed that there was no correlation between knowledge, physical activity and nutrition status with the incidence of hyperuricemia (p >0.05).Â  Suggest for the next researcher to do reaserch on respondent with heavy physical activity to see its effect on elevated levels of uric acid.